Ferrites at microwave frequencies - Baden Fuller, A. J. (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1987)
This book discusses the magnetised ferrite in waveguides; Y-junction circulators; stripline and microstrip devices and; perturbation theory and measurements.
Electronic reproduction.
Keywords: Ferrite devices; Microwaves; Electronic books